2014
DOI: 10.1002/2014ja019884
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER observations of large dayside flux transfer events: Do they drive Mercury's substorm cycle?

Abstract: The large-scale dynamic behavior of Mercury's highly compressed magnetosphere is predominantly powered by magnetic reconnection, which transfers energy and momentum from the solar wind to the magnetosphere. The contribution of flux transfer events (FTEs) at the dayside magnetopause to the redistribution of magnetic flux in Mercury's magnetosphere is assessed with magnetic field data acquired in orbit about Mercury by the Magnetometer on the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 69 publications
(91 reference statements)
9
96
1
Order By: Relevance
“…These values are lower than previous estimates (e.g., DiBraccio, Slavin, Raines, et al, ; Imber et al, ). However, our study includes all MESSENGER observations and does not focus on large amplitude events (such as the large FTEs observed by Imber et al, and the large mantle dispersion observed by DiBraccio, Slavin, Raines, et al, ). Therefore, our study includes quiet magnetospheric conditions as well as the extreme events.…”
Section: Observationscontrasting
confidence: 71%
See 1 more Smart Citation
“…These values are lower than previous estimates (e.g., DiBraccio, Slavin, Raines, et al, ; Imber et al, ). However, our study includes all MESSENGER observations and does not focus on large amplitude events (such as the large FTEs observed by Imber et al, and the large mantle dispersion observed by DiBraccio, Slavin, Raines, et al, ). Therefore, our study includes quiet magnetospheric conditions as well as the extreme events.…”
Section: Observationscontrasting
confidence: 71%
“…Large fluctuations in the magnetic field data can be seen at the magnetopause (the magnetopause is marked by the middle and right vertical dashed lines), as well as in the plasma sheet. These are largely due to the presence of flux ropes, with flux transfer events being observed at the magnetopause and plasmoids in the plasma sheet (e.g., DiBraccio, Slavin, Imber, et al, ; Imber et al, ; Slavin et al, ), as well as dipolarization fronts in the plasma sheet (Sun et al, ; Sundberg et al, ).…”
Section: Observationsmentioning
confidence: 99%
“…These FTEs being swept into the magnetotail at a rate of 0.5 per second implies a mean contribution to Mercury's cross-magnetospheric potential drop is 16 kV. Further, this FTE flux transfer rate is comparable to that estimated for the non-FTE magnetic flux being transferred to the magnetotail (DiBraccio et al, 2013;Imber et al, 2014;Slavin et al, 2009). Further, this FTE flux transfer rate is comparable to that estimated for the non-FTE magnetic flux being transferred to the magnetotail (DiBraccio et al, 2013;Imber et al, 2014;Slavin et al, 2009).…”
Section: Ddm Flux Transfer Eventsmentioning
confidence: 56%
“…Mariner 10 and MESSENGER flyby data suggested strongly that substorm‐like events occur in Mercury's magnetosphere, but on a time scale much shorter, ~2–3 min, than at Earth [ Siscoe et al , ; Slavin et al , ]. Measurements from the MESSENGER spacecraft [ Slavin et al , , , ; DiBraccio et al , ; Imber et al , ] have demonstrated convincingly that strong magnetic reconnection occurs at Mercury between the incident interplanetary magnetic field and the dayside Mercury magnetic field. Reconnection events and flux transfer event signatures at the dayside magnetopause, as well as “plasmoids” and magnetic traveling compression regions on the nightside, clearly demonstrate and extend our understanding of the dynamic nature of Mercury's magnetosphere.…”
Section: Discussionmentioning
confidence: 99%